Analysis of Economic Feasibility and Compressive Strength of Concrete Based on the Utilization of Red Mud Waste and Sustainable Construction Management - Muhamad Reza Maulana; Agus Suroso (Green Publisher Indonesia, 2026)
This research examines red mud as a partial cement substitute in concrete, comparing normal concrete with 25% red-mud concrete (RM25) based on compressive strength, economic feasibility, waste absorption, and LCA environmental impact. Compressive strength tests were conducted at KAN-accredited Wika Beton Laboratory, and economic feasibility was evaluated using NPV, BCR, and IRR for paving-block production. The waste absorption capacity was calculated based on an annual production volume of 5,000 m². The LCA assessment was carried out in accordance with ISO 14040:2006, covering goal and scope definition, life cycle inventory (LCI), life cycle impact assessment (LCIA), and interpretation. The results showed that RM25 achieved a compressive strength of 36.93 MPa at 30 days, higher than normal concrete with 34.15 MPa. Economically, RM25 recorded a production cost of IDR 1,480,085/m³, with a positive NPV, an IRR of 43.9%, and BCR > 1. In addition, RM25 enabled the absorption of approximately 41.8 tons of red mud waste per year in paving-block production. The LCA results also indicated a reduction in environmental impacts, particularly in the global warming potential category, due to reduced cement consumption. Overall, the 25% red-mud formulation is considered feasible for practical implementation as it meets both technical and economic requirements while providing environmental benefits through emission reduction and enhanced industrial waste utilization.